Zinc oxide nanoparticles decorated fluorescent and antibacterial glass fiber pre-filter paper - Gupta A.; Mishra V.; Srivastava R. (My University, 2025)
Zinc oxide nanoparticles (ZnO-NPs) were synthesized and decorated simultaneously onto the glass fiber pre-filter paper (GF paper) by the sonochemical method without using any additional reagents (a 'Green' synthesis approach). ZnO-NPs decorated GF paper was characterized by electron, confocal laser scanning and atomic force microscopy, fourier transform infrared and atomic emission spectroscopy, X-ray diffraction, and thermogravimetric analysis etc. Due to the massive void volume space, exceptional dimensional stability, large thickness (790 μm) of the GF paper (unlike other paper materials) and ultrasonic irradiation effects, ZnO-NPs were decorated in the enormous amount (96 mg per paper) without causing any adverse effects on the GF paper. Such a huge amount decoration onto GF paper makes it multifunctional, fluorescencet (orange-pink color, 535-624 nm) under ultra-violet light (360 nm) and antibacterial. The antibacterial activity of the ZnO-NPs decorated GF paper was examined against Gram-positive bacteria Bacillus subtilis 168 and Staphylococcus aureus (MCC 2043, pathogenic). The outcomes from the antibacterial experiments revealed 1/499% (2 log) reduction in the survival of the filtered bacteria (B. subtilis) on the ZnO-NPs decorated GF paper due to the toxicity of ZnO-NPs on bacterial cells like cell shrinkage, cytoplasmic leakage, cell burst, etc. Multifunctional, ZnO-NPs decorated GF paper could be used for fluorescencet and antibacterial paper-based applications. © 2020 The Author(s). Published by IOP Publishing Ltd